Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,3^x=\frac{9^4}{27^3}\)
\(\Leftrightarrow3^x=3^8:3^9\)
\(\Leftrightarrow3^x=3^{-1}\)
\(\Leftrightarrow x=-1\)
\(b,\frac{5^5}{5^x}=5^{18}\)
\(\Leftrightarrow5^x=5^5:5^{18}\)
\(\Leftrightarrow5^x=5^{-13}\)
\(\Leftrightarrow x=-13\)
A;3x=94/(9*3) 3=94=93*33=93*9=94
3X=94=38
X=8
B;55/5x=518=55-x
=>5-x=18
x=5-18
x=-13
c: \(=\dfrac{7}{23}\cdot\left(\dfrac{-4}{3}-\dfrac{5}{2}\right)=\dfrac{7}{23}\cdot\dfrac{-8-15}{6}\)
\(=\dfrac{7}{23}\cdot\dfrac{-23}{6}=-\dfrac{7}{6}\)
d: \(=\dfrac{5}{7}\left(23+\dfrac{1}{4}-13-\dfrac{1}{4}\right)=\dfrac{5}{7}\cdot10=\dfrac{50}{7}\)
e: \(=\dfrac{2^5\cdot3^3\cdot5^3}{2^3\cdot3^3\cdot2^2\cdot5^2}=5\)
i: \(=\dfrac{1}{3^{10}}\cdot3^{50}-\dfrac{2^{10}}{3^{10}}:\dfrac{4^5}{3^{10}}\)
\(=3^{40}-1\)
c: \(=\dfrac{7}{23}\cdot\dfrac{-24-45}{18}=\dfrac{7}{23}\cdot\dfrac{-69}{18}=\dfrac{7}{18}\cdot\left(-3\right)=-\dfrac{7}{6}\)
d: \(=\dfrac{7}{5}\left(23+\dfrac{1}{4}-13-\dfrac{1}{4}\right)=\dfrac{7}{5}\cdot10=14\)
e: \(=\dfrac{2^5\cdot3^3\cdot5^3}{2^3\cdot3^3\cdot2^2\cdot5^2}=5\)
i: \(=\dfrac{1}{3^{10}}\cdot3^{50}-\dfrac{2^{10}}{3^{10}}:\dfrac{4^5}{9^5}=3^{40}-1\)
\(8^{15}\times4^{13}=2^{45}\times2^{26}=2^{71}\)
\(\left(\frac{1}{2}\right)^{18}\times\left(\frac{1}{4}\right)^{24}=\left(\frac{1}{2}\right)^{18}\times\left(\frac{1}{2}\right)^{48}=\left(\frac{1}{2}\right)^{66}\)
\(9^{12}\times27^{10}=3^{24}\times3^{30}=3^{54}\)
\(8^{15}\cdot4^{13}=\left(4^2\right)^{15}\cdot4^{13}=4^{30}\cdot4^{13}=4^{43}\)
\(\left(\frac{1}{2}\right)^{18}\cdot\left(\frac{1}{4}\right)^{24}=\left(\frac{1}{2}\right)^{18}\cdot\left[\left(\frac{1}{2}\right)^2\right]^{24}=\left(\frac{1}{2}\right)^{66}\)
\(9^{12}\cdot27^{10}=3^{36}\cdot3^{30}=3^{66}\)
a, \(\dfrac{4^2.4^3}{2^{10}}=\dfrac{4^5}{2^{10}}=\dfrac{\left(2^2\right)^5}{2^{10}}=\dfrac{2^{10}}{2^{10}}=1\)
b, \(\dfrac{2^7.9^3}{6^5.8^2}=\dfrac{2^7.\left(3^2\right)^3}{2^5.3^5.\left(2^3\right)^2}=\dfrac{2^7.3^6}{2^5.3^5.2^6}=\dfrac{3}{2^4}=\dfrac{3}{16}\)
c, \(\dfrac{9^7.5^6.125^9}{15^{15}.5^{18}}=\dfrac{3^{21}.5^6.5^{27}}{5^{15}.3^{15}.5^{18}}=\dfrac{3^{21}.5^{33}}{3^{15}.5^{33}}=3^6=729\)
d, \(\dfrac{4^6.9^5+6^9.120}{8^4.3^{12}-6^{11}}=\dfrac{2^{12}.3^{10}+2^9.3^9.2^3.3.5}{2^{12}.3^{12}-2^{11}.3^{11}}\)
\(=\dfrac{2^{12}.3^9.\left(1+3.5\right)}{2^{11}.3^{11}.\left(2.3-1\right)}=\dfrac{2.16}{3^2.5}=\dfrac{32}{45}\)
Chúc bạn học tốt!!!
a: \(\Leftrightarrow4^x\left(\dfrac{3}{2}+\dfrac{5}{3}\cdot4^2\right)=4^8\left(\dfrac{3}{2}+\dfrac{5}{3}\cdot4^2\right)\)
=>4^x=4^8
=>x=8
b: \(\Leftrightarrow2^x\cdot\dfrac{1}{2}+2^x\cdot2=2^{10}\left(2^2+1\right)\)
=>2^x=2^11
=>x=11
c: =>1/6*6^x+6^x*36=6^15(1+6^3)
=>6^x=6*6^15
=>x=16
d: \(\Leftrightarrow8^x\left(\dfrac{5}{3}\cdot8^2-\dfrac{3}{5}\right)=8^9\left(\dfrac{5}{3}\cdot8^2-\dfrac{3}{5}\right)\)
=>x=9
\(\dfrac{3^{18}.24^4}{18^4.9^5}=\dfrac{3^{18}.6^4.4^4}{3^4.6^4.\left(3^2\right)^5}\\ =\dfrac{3^{18}.6^4.4^4}{3^4.6^4.3^{10}}\\ =\dfrac{3^{18}.6^4.4^4}{3^{14}.6^4}=3^4.4^4=12^4\)
\(\dfrac{3^{18}.24^4}{18^4.9^5}=\dfrac{3^{18}.3^4.8^4}{9^4.2^4.9^5}=\dfrac{3^{22}.\left(2^3\right)^4}{\left(3^2\right)^9.2^4}=\dfrac{3^{22}.2^{12}}{3^{18}.2^4}=3^4.2^8\)